Uneven onset and pace of ice‐dynamical imbalance in the Amundsen Sea Embayment, West Antarctica. Issue 2 (26th January 2017) - Konrad, Hannes; Gilbert, Lin; Cornford, Stephen L.; Payne, Antony; Hogg, Anna; Muir, Alan; Shepherd, Andrew
Abstract: We combine measurements acquired by five satellite altimeter missions to obtain an uninterrupted record of ice sheet elevation change over the Amundsen Sea Embayment, West Antarctica, since 1992. Using these data, we examine the onset of surface lowering arising through ice‐dynamical imbalance, and the pace at which it has propagated inland, by tracking elevation changes along glacier flow lines. Surface lowering has spread slowest (<6 km/yr) along the Pope, Smith, and Kohler (PSK) Glaciers, due to their small extent. Pine Island Glacier (PIG) is characterized by a continuous inland spreading of surface lowering, notably fast at rates of 13 to 15 km/yr along tributaries draining the southeastern lobe, possibly due to basal conditions or tributary geometry. Surface lowering on Thwaites Glacier (THG) has been episodic and has spread inland fastest (10 to 12 km/yr) along its central flow lines. The current episodes of surface lowering started approximately 10 years before the first measurements on PSK, around 1990 on PIG, and around 2000 on THG. Ice‐dynamical imbalance across the sector has therefore been uneven during the satellite record. Key Points: Upstream propagation of ice‐dynamical imbalance on the glaciers in the ASE has not been uniform Imbalance has spread 2 times faster along PIG's SE tributaries and THG's central section than elsewhere Recent episodes began around 1990 on PIG, around 2000 on THG, and around 1980 in PSK